Cereals processing technology (Woodhead, 2001)
This text provides an overview of current and emerging technologies and equipment. The nine contributors represent both academia and industry in the UK. They cover cereal and flour production; wheat, corn, and coarse grains milling; biotechnology, cereal, and cereal product quality; rice, pasta, and Asian noodle processing; breakfast cereals; malting; and breadmaking